(untitled) (Movimenta (ISSN 1984-4298), 2024)
Objective: To characterize the environmental factors and the functionality profile of children and adolescents with cerebral palsy (CP) enrolled in a public university physiotherapeutic rehabilitation service. Methodology: Children and adolescents with CP and their guardians participated in this cross-sectional observational study. The characterization of the sample and information about environmental factors were obtained from a questionnaire developed by the researchers. The functionality profile was drawn from the Gross Motor Function (GMFCS) and Manual Ability (MACS) classification systems, and through the Gross Motor Function Measure-Version 88 (GMFM-88), which assesses gross motor function. Results: 13 children and adolescents with CP participated, with a mean age of 9.7 years, 76.9% with bilateral spastic neurological subtype and 53.8% quadriparetic. The functionality profile was characterized by limitations in locomotion and manual function. Access to orthoses (84.5%), wheelchairs (84.6%), health and school services (100%), and medications (53.8%) were identified as facilitators. The barriers were the presence of stairs in the home (38.5%) and the lack of ramps in the home (76.9%). Conclusion: Even in an environment with more facilitators than barriers, children and adolescents with CP presented limitations in locomotion and manual function, reinforcing the need for this population to be continuously assisted by health services.